1993
DOI: 10.1007/bf01244939
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in sensitivity to methamphetamine toxicity

Abstract: Male and female mice were treated with methamphetamine (10.0 mg/kg/injection for four injections) and sacrificed two weeks later. It was observed that the methamphetamine treatment caused depletions in striatal dopamine which were significantly greater in males (74%) than in females (56%). These results indicate that estrogen may have a protective effect against methamphetamine-induced dopamine depletions and may relate to the fact that males are more likely to incur Parkinson's disease than females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 11 publications
6
56
0
Order By: Relevance
“…While remaining cognizant of these limitations, data derived from these animal experiments have served as relatively valid and reliable models for indices of effects in humans. Women show less toxicity [17] and diminished dopamine responses [18] to MA/amphetamine as compared with men, which is similar to that of results obtained with mice [19,20]. Of particular relevance to the present report, are the findings indicating that weight loss is a pervasive characteristic of MA, as seen in mice and humans [1][2][3][4][5][6].…”
supporting
confidence: 77%
“…While remaining cognizant of these limitations, data derived from these animal experiments have served as relatively valid and reliable models for indices of effects in humans. Women show less toxicity [17] and diminished dopamine responses [18] to MA/amphetamine as compared with men, which is similar to that of results obtained with mice [19,20]. Of particular relevance to the present report, are the findings indicating that weight loss is a pervasive characteristic of MA, as seen in mice and humans [1][2][3][4][5][6].…”
supporting
confidence: 77%
“…Since Wagner et al [3]reported the sexual differences in the sensitivity to MA-induced striatal DA toxicity, the developmental time window of sex hormone influences in establishing these differences has remained elusive. We now demonstrate that the sexual differences could be determined between 4 and 6 weeks postpartum through two lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this MA-induced striatal DA depletion was reduced in adult female as compared to adult male mice [3, 4]. However, no such sexual difference in the sensitivity to MA-induced striatal DA depletion in Swiss Webster mice gonadectomized on day 20 of life was observed in a preliminary study.…”
Section: Introductionmentioning
confidence: 97%
“…Males have been reported to be more susceptible to neurotoxic effects of MA in animal studies (Hirata et al, 1996;Wagner et al, 1993). Recently, Chang et al (2002) have reported that male MA users had decreased rCBF and female MA users had increased rCBF in occipital and midline structures, relative to gender-matched comparison subjects (Chang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%